Distributed Web Service Architecture towards Robotic Speech Communication: A Vietnamese Case Study. (15th February 2013) - Pham, Nhut M.; Dau, Duong N.H.; Vu, Quan H.
Robotics is emerging as one of the most prominent research areas in the world and is recently attracting the Vietnamese research community. For the purpose of determining an entrance for a Vietnamese human interacting robotics system, this paper is aimed at proposing a service-oriented architecture for location assistance robotic systems made out of loosely-coupled and distributed web services. The proposed platform consists of two major components: a Speech Processing System (SPS) and a Service Manipulating System (SMS). This architecture allows our robot to meet three critical human interaction robotic systems requirements: flexibility, scalability and reliability.